IMPERATIVES OF RAISING THE ANTE OF LEGAL REGULATIONS OF HUMAN RESOURCES PRACTICE IN NIGERIA (Singaporean Journal of Business Economics and Management, 2012)
This paper is an analysis of the multi-dimensional relationships of the field of Human Resources (HR) practice and the field of law as well as the areas of their inter-twinning intercourse within the statutory and judicial framework of the Nigerian legal system. The contact points between these two fields as identified by this work includes regulations on job placements and vacancy advertisements, terms of job offers, acceptance, capacity to contract and legality or otherwise of employment contracts. The paper found that there is constitutional provision for labour and human resources practices that sufficiently protect the employees and employers but the implementation particularly in small and medium size organizations in a situation of high unemployment ratio is a huge challenge. The paper concludes the challenges are not insurmountable but recommends the imperatives of an increased level of fidelity in the application of extant laws regulating HR practice and management in Nigeria.